Synergistic Processing of Biphenyl and Benzoate: Carbon Flow Through the Bacterial Community in Polychlorinated-Biphenyl-Contaminated Soil - Leewis, Mary-Cathrine; Uhlik, Ondrej; Leigh, Mary Beth (Scientific reports, 2016)
Aerobic mineralization of PCBs, which are toxic and persistent organic pollutants, involves the upper (biphenyl, BP) and lower (benzoate, BZ) degradation pathways. The activity of different members of the soil microbial community in performing one or both pathways, and their synergistic interactions during PCB biodegradation, are not well understood. This study investigates BP and BZ biodegradation and subsequent carbon flow through the microbial community in PCB-contaminated soil. DNA stable isotope probing (SIP) was used to identify the bacterial guilds involved in utilizing (13)C-biphenyl (unchlorinated analogue of PCBs) and/or (13)C-benzoate (product/intermediate of BP degradation and analogue of chlorobenzoates). By performing SIP with two substrates in parallel, we reveal microbes performing the upper (BP) and/or lower (BZ) degradation pathways, and heterotrophic bacteria involved indirectly in processing carbon derived from these substrates (i.e. through crossfeeding). Substrate mineralization rates and shifts in relative abundance of labeled taxa suggest that BP and BZ biotransformations were performed by microorganisms with different growth strategies: BZ-associated bacteria were fast growing, potentially copiotrophic organisms, while microbes that transform BP were oligotrophic, slower growing, organisms. Our findings provide novel insight into the functional interactions of soil bacteria active in processing biphenyl and related aromatic compounds in soil, revealing how carbon flows through a bacterial community.
Keywords: látky znečišťující půdu; benzoáty; biodegradace; RNA, Ribosomal, 16S; Biodegradation, Environmental; nebezpečný odpad; RNA ribozomální 16S; Bacteria; polychlorované bifenyly; půda; aromatické uhlovodíky; Polychlorinated Biphenyls; Soil Microbiology; půdní mikrobiologie; Soil; Benzoates; Biphenyl Compounds; Hazardous Waste; Hydrocarbons, Aromatic; znečištění životního prostředí; Soil Pollutants; Environmental Pollution; bifenylové sloučeniny